2022
DOI: 10.29219/fnr.v66.8851
|View full text |Cite
|
Sign up to set email alerts
|

Açaí (Euterpe oleracea) pulp-enriched diet induces anxiolytic-like effects and improves memory retention

Abstract: Background: Açaí (Euterpe oleracea) has a rich nutritional composition, showing nutraceutical and protective effects in several organs. In this study, the effects of an açaí-enriched diet on motor performance, anxiety-like behavior, and memory retention were deeply investigated. Methods: Eight-week male Wistar rats were fed with an Euterpe oleracea (EO) pulp-enriched diet, an olive oil-enriched (OO) diet (polyunsaturated fatty acid [PUFA] fat control diet), or a chow diet for 31 days (28 days pre-treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Our data mainly showed that the retinal functional responses of diabetic animals that received açaí-enriched diet did not statistically differ from the responses of the control groups in almost all protocols tested (except in cone response at day 60), these results demonstrate a potential neuroprotective effect of açaí against the damage promoted by diabetes in the retina, reflecting on the preservation of retinal function. The present result about mass body corroborates the previous studies carried out by our group using a similar fortified feed that showed that EO-enriched diet did not influence the animals mass body ( Brasil et al, 2017 ; de Carvalho et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our data mainly showed that the retinal functional responses of diabetic animals that received açaí-enriched diet did not statistically differ from the responses of the control groups in almost all protocols tested (except in cone response at day 60), these results demonstrate a potential neuroprotective effect of açaí against the damage promoted by diabetes in the retina, reflecting on the preservation of retinal function. The present result about mass body corroborates the previous studies carried out by our group using a similar fortified feed that showed that EO-enriched diet did not influence the animals mass body ( Brasil et al, 2017 ; de Carvalho et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, recently our group showed that E. oleracea -enriched diet provided anxiolytic-like effects and improves memory consolidation in rats, probably due to the reduced levels of lipid peroxidation (markers of oxidative damage) in the hippocampus ( de Carvalho et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations